Diagnosing Effect of English Novels on Augmenting EFL Learners’ Language Skills and Competencies - Yalmiadi Yalmiadi; Rahma Yanti; Toni Indrayadi; Wahyudi Rahmat (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2021)
English novels add new dimensions to augmenting the second language or foreign language learners’ skills and competencies. However, English novels have little roles in the Indonesian ELT context and gradually fade away from Indonesian EFL learning’s programs today. This study, therefore, aimed at diagnosing the effects of English novels on augmenting EFL learners’ language skills and competencies. This research entailed a qualitative research approach. The English Department (ED) students numbering 20 were the research participants. The interviews, focus groups, and participant observation were the key techniques of collecting data. The 1994 Miles and Huberman model of data display, data reduction, and conclusion were stages of analyzing the data. The findings show that reading English novels extensively and intensively develop the ED students’ language skills of higher thinking skills, vocabulary acquisition, and productive-receptive skills of English and linguistic and pragmatic competencies. In conclusion, English novels discover a love of the language, practically improve and develop the 2nd-year ED students’ exposure to English language and lead them to communicate like native English speakers.